Comparison of Berlin Questionnaire, STOP-Bang, and Epworth Sleepiness Scale for Diagnosing Obstructive Sleep Apnea in Persian Patients - Amra, Babak (Int J Prev Med, 2018)
BACKGROUND: Obstructive sleep apnea (OSA) is a common disorder characterized by snoring, daytime sleepiness, fatigue, and repeated termination of airflow (apnea). Standard polysomnography (PSG) is diagnostic gold standard for OSA. PSG is expensive and not available everywhere. To identify the best OSA questionnaire for screening in Persian population, we compared Berlin, STOP-BANG, and Epworth Sleepiness Scale (ESS). METHODS: In a cross-sectional study conducted on 400 adult patients suspected of OSA in Bamdad Respiratory Research Center, patients completed three questionnaires. For each questionnaire, patients were divided into high risk and low risk. Then, PSG was performed for all patients. According to PSG, patients categorized into without OSA (apnea-hypopnea index [AHI] <5), mild OSA (15> AHI ≥5), moderate OSA (30> AHI ≥15), and severe OSA (AHI ≥30). Based on questionnaires and PSG results, predictive parameters for screening tests were calculated. RESULTS: There were 234 (58.5%) males and 166 (41.5%) females in study population. Mean age of patients was 49.29 ± 9.75 standard deviation years. There was significant association between age with OSA (P = 0.005) and between body mass index (BMI) and neck circumference, with moderate and severe OSA (P < 0.001). Sensitivities of Berlin, STOP-BANG, and ESS were 86.42%, 81.46%, and 59%, respectively. Specificities of Berlin, STOP-BANG, and ESS were 52.94%, 82.35%, and 76.47%, respectively. CONCLUSIONS: This study suggested that Berlin and STOP-BANG are more sensitive and accurate than ESS for OSA screening in Iran.